1994
DOI: 10.1149/1.2055106
|View full text |Cite
|
Sign up to set email alerts
|

2% Platinum ‐  H 2 WO 4 Based Electrocatalysts for Phosphoric Acid Fuel‐Cell Cathode

Abstract: A normalPt‐H2WO4 based electrocatalyst has been fabricated by an inexpensive chemical route for use as an oxygen cathode in 99% phosphoric acid at 180°C. The effect of %Pt (w/w) and %H2WO4 (w/w) on the normalPt‐H2WO4 electrode performance was studied. The electrocatalytic properties for the oxygen reduction reaction, e.g., exchange current density, mass activity, and specific activity of a 2% normalPt‐H2WO4 based electrode was several times higher than those of 10% Pt. The performance of the 2% normalP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Kinetic parameters from Tafel plot with mass transfer corrected data were used to determine the exchange current density (mA/cm 2 ) and Tafel slope (mV/dec). It is well known that the total ORR current could be split in two terms, one relative to the kinetic current (i k ) and the other one relative to the diffusion limiting current (i lim ) [23,24] as following:…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic parameters from Tafel plot with mass transfer corrected data were used to determine the exchange current density (mA/cm 2 ) and Tafel slope (mV/dec). It is well known that the total ORR current could be split in two terms, one relative to the kinetic current (i k ) and the other one relative to the diffusion limiting current (i lim ) [23,24] as following:…”
Section: Resultsmentioning
confidence: 99%
“…During the past few years, significant developments on electrode modification by POMs have taken place aiming to improve the reaction rates of fuel cells and produce economically sufficient currents for practical uses. [193][194][195][196][197] Electrocatalysts that are incorporated into the fuel cell electrodes are required to have high activity for the electrochemical reduction of oxygen, as well as being able to withstand a working environment of relatively high temperatures and strong acid levels. Recent work by Savadogo et al has shown that POMs exhibit these attributes.…”
Section: Electrode Modification By Pomsmentioning
confidence: 99%
“…has shown that POMs exhibit these attributes. In two recent patents he described the fabrication and performance of polycomponent electrodes for electrochemical and fuel cells. , The electrodes were made on a chemically treated graphite support, via treatment with chloroplatinic acid or chloropalladic acid, followed by treatment with a POM solution at various concentrations. A binder waterproofing agent such as poly(tetrafluoroethylene) (Teflon) was also used as additional catalyst support.…”
Section: Electrode Modification By Pomsmentioning
confidence: 99%
“…Attempts to improve the performance of the Pt catalyst have involved alloying it with transition metals [3][4][5][6][7][8][9][10][11][12] and mixing it with acid resistant oxides such as WO 3 . [13][14][15][16] Although all of these efforts resulted in improved performance, the mechanism of the improvement is not clear. Furthermore, it has been observed that such alloys are invariably corroded, releasing transition metal ions into the electrolyte.…”
mentioning
confidence: 99%